Microbial surface tensio-active compounds: Production and industrial application perspectives: A review - Mir, Shajrat; Jamal, Parveen; Alam, Md. Zahangir; Mir, Aarif Bashir; Ansari, Abdul Haseeb (BioCore, 2017)
Biosurfactants are surface active agents produced naturally by a wide variety of microorganisms, which include different strains of bacteria, fungi and yeast. Biosurfactants, also known as microbial surfactants, are amphiphilic compounds. It is the amphiphilic nature of biosurfactants that makes them excellent foaming, emulsifying and dispersing agents. The .0surfactants or biosurfactants increase the surface area of the water-insoluble hydrophobic entities. They are surpassing their chemical counterparts. This can be attributed to diversity, high biodegradability, less toxicity, greater stability and ecological acceptance of biosurfactants in comparison with the chemically prepared surfactants. However, currently, production of biosurfactants is a very expensive process mainly because of the costly synthetic media required by the microorganisms to survive and grow. Therefore, much stress is being put on augmenting researching on cheap or cost free and nutrient rich renewable wastes to be used as substrates for various microbes to grow and produce biosurfactants. Research for new strains with high productivity is a challenge for the widespread application of microbial surfactants. This review focuses on the extensive evaluation of biosurfactants and their application on commercial scale.